A matemática financeira no contexto do novo ensino médio numa perspectiva freiriana - Cabral, Pedro Caixeta (2023)
This dissertation is based on the need to promote Mathematics teaching based on a liberating education proposal. This need takes as a discussion bias the educational perspective defended by Paulo Freire, especially in the understanding of a dialogical and problematizing formation. The problem of the study is to bring the Freirean approach to the classroom as a structuring of Financial Mathematics classes linked to the New Brazilian High School. This problem leads to the following research question: what assessment do teachers make of an approach to Financial Mathematics concepts associated with the context of New High School, within a Freirean perspective? The objective of the study is to provide a permanent training course for Mathematics teachers, to review specific Financial Mathematics content included in the New High School, based on a Freirean didactic approach, evaluating the relevance of the approach and proposed activities. To this end, a theoretical basis is sought in the works of Paulo Freire, in the relationships between Financial Mathematics and Critical Mathematics Education and in the legal documents that govern national education, especially those linked to the Federal District. In didactic terms, the activities presented to teachers, and which are the object of evaluation in the present study, are guided by the approach of the Three Pedagogical Moments (3MP) in the understanding of Delizoicov and Angotti (1990), structured in didactic sequences which were discussed in an ongoing training course. The course, which was endorsed by the State Department of Education of the Federal District (SEEDF), had the participation of eight Mathematics teachers and had a workload of 30 hours with synchronous face-to-face and virtual meetings and also asynchronous activities. In order to answer the research question, the study is based on qualitative descriptive research, using the following instruments to produce data: two forms answered by teachers participating in the training course offered; recordings of course meetings; and, semi-structured interviews with participants. For analysis of the data produced, three categories given a priori are structured, namely: Freirian pedagogical conception; didactic-methodological organization; and educational product. This last category infers the existence of an Educational Product related to this dissertation and which is associated with a set of activities organized from the perspective of the 3MP and which seek to provide support for the didactic action of teachers in Mathematics classes, specifically related to Financial math. The results obtained indicate that the 3MP approach associated with the Freirean approach given to the concepts of Financial Mathematics proved to be adequate and pertinent, showing that it provides opportunities for teaching focused on the students' reality and that values ​​dialogicity, reflection, criticality and protagonism of these students. Furthermore, what was presented proved to provoke movement within the school community, which, by adhering to a liberating education, discusses and guides public policies, especially educational ones, in our case. Finally, the study highlighted the potential of the teaching material developed in the form of an Educational Product, especially in terms of its use as a teaching resource for Financial Mathematics classes. This product is available on the PPGECM/UPF page and in the EduCapes repository.